(untitled) (ItalianoLinguadue, 2020)
Con il presente contributo si intendono analizzare gli errori grammaticali e sintattici e le imprecisioni lessicali degli studenti cinesi del Programma Marco Polo presso il Corso di laurea in mediazione linguistica e culturale. In particolare, vengono analizzate le traduzioni dal cinese all’italiano proposte all’esame scritto del terzo anno e presi in esame anche alcuni passi degli elaborati finali e delle tesi magistrali. Introduce il contributo una breve presentazione del sistema scolastico cinese in modo da comprendere il background di istruzione. The approach to Italian translation by Chinese students enrolled in the degree in language mediation and intercultural communication This paper analyzes grammar and syntactical mistakes as well as lexical inaccuracies made by Chinese students in the Marco Polo Program attending the degree course in Linguistic and Cultural Mediation. Specifically, Chinese to Italian translations from written tests given during the third year and some excerpts from doctoral thesis are analyzed in-depth. A brief introduction to the organization of the Chinese education system is also presented to promote understanding of the learners’ backgrounds.